Bibliometric Analysis of Digital Agricultural Research Knowledge Maps in the Global Agricultural Sector - Loso Judijanto (West Science Agro, 2026)
Digital agriculture has emerged as a transformative approach for improving agricultural productivity, resource efficiency, and sustainability through the integration of advanced digital technologies. The rapid growth of research in this field has generated a diverse and multidisciplinary body of knowledge, making it increasingly important to understand its intellectual structure and developmental trends. This study aims to analyze the global landscape of digital agriculture research using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to identify publication trends, influential publications, collaboration networks, and thematic developments within the field. The results indicate a significant increase in scholarly interest in digital agriculture, particularly in topics related to artificial intelligence, precision agriculture, smart farming, the Internet of Things (IoT), digital transformation, and sustainable development. Country collaboration analysis reveals that China, India, the Russian Federation, the United States, Germany, Italy, and the United Kingdom are among the leading contributors to knowledge production and international research cooperation. Citation analysis highlights the foundational role of studies on big data, Agriculture 4.0, and smart farming in shaping the field's intellectual development. Furthermore, keyword co-occurrence, overlay, and density visualizations demonstrate that research has evolved from digital infrastructure and data management toward advanced technologies such as machine learning, deep learning, blockchain, and intelligent decision-support systems. The findings suggest that digital agriculture has become a dynamic and interdisciplinary research domain that integrates technological innovation with agricultural sustainability and food security objectives. This study contributes to the understanding of global research trends and provides valuable insights for researchers, policymakers, and practitioners seeking to advance the digital transformation of agriculture.